Gambaran Hasil Pemeriksaan Sitologi Cairan Asites di Instalasi Patologi Anatomi RSUD Arifin Achmad Provinsi Riau Periode Januari 2013 – Desember 2017 - Ilhami Romus; Ina Farida Rangkuti; Vini Jum’atur Rahmah (Fakultas Kedokteran Universitas Riau, 2019)
Ascites is abnormal accumulation fluid in the peritoneal cavity. Many underlying disease can be responsible for causing ascites. Peritoneal fluid cytology remains the gold standard for detection of malignant cells in ascites which is useful in determining staging, treatment and prognosis. This aim of this study is to describe the characteristic of the result ascitic cytology examination at Anatomical Pathology Department of Arifin Achmad Hospital Period January 2013 – December 2018. This study reviewed the anatomy pathology data. A total of 171 cases consisted of 91.8% were females and males were 8.2%. The highest number cases were in the age group of 41-50 years (26.9%). Most ascitic fluid came from Department of Obstetric and Gynecology (81.9%). The more frequent clinical diagnosis were ovarian carcinoma (19.3%) and ovarian cyst (18.7%). Most ascitic cytology examination results was positive cytology (64,9%). Adenocarcinoma was commonest positive cytology (46,2%).